2020
DOI: 10.3892/etm.2020.8881
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of long non‑coding RNA expression profiles in patients with post‑menopausal osteoporosis by RNA sequencing

Abstract: The present study aimed to investigate the implication of long non-coding RNA (lncRNA) expression profiles in post-menopausal osteoporosis (PMOP). A total of 10 patients with PMOP and 10 age-matched healthy post-menopausal females as controls were consecutively enrolled. Their peripheral blood mononuclear cells were obtained and lncRNA as well as mRNA expression profiles were detected by RNA sequencing, followed by bioinformatics analyses. The lncRNA expression profiles were able to distinguish patients with P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Although some differentially expressed genes were shared between T2D and control samples ( Figure 3 B), 181 up- and 179 down-regulated genes were differentially regulated specifically in T2D compared to the control samples, including 35 up- and 22 down-regulated lncRNA genes ( Supplementary Table S6 ). Among these up-regulated lncRNA genes, only the following nine have been previously studied: (1) ENSG00000232855 (novel transcript) [ 75 ]; (2) ENSG00000272512 (novel transcript) [ 76 ]; (3) KCNJ2 antisense RNA 1 (KCNJ2-AS1) [ 77 , 78 , 79 ]; (4) KLHDC7B divergent transcript (KLHDC7B-DT) [ 80 , 81 , 82 ]; (5) long intergenic non-protein-coding RNA 2015 (LINC02015) [ 83 , 84 ]; (6) long intergenic non-protein-coding RNA 2381 (LINC02381) [ 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 ]; (7) long intergenic non-protein-coding RNA 2541 (LINC02541) [ 94 ]; (8) serpin family B member 9 pseudogene 1 (SERPINB9P1) [ 95 , 96 , 97 ]; and (9) USP30 antisense RNA 1 (USP30-AS1) [ 98 , 99 , 100 ]. However, only the functions of the lncRNA genes LINC02381 and USP30_AS1 are known, with the former known to bind transcription factors [ 85 ], RNA-binding proteins [ 86 ], and miRNAs [ 87 , 88 , 89 , 90 , 91 , 92 , 93 ]; while USP30-AS1 acts as a miRNA sponge [ 98 , 99 ] and is involved in the cis-regulation of the nearby protein-coding genes USP30 and ANKRD13A [ 100 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although some differentially expressed genes were shared between T2D and control samples ( Figure 3 B), 181 up- and 179 down-regulated genes were differentially regulated specifically in T2D compared to the control samples, including 35 up- and 22 down-regulated lncRNA genes ( Supplementary Table S6 ). Among these up-regulated lncRNA genes, only the following nine have been previously studied: (1) ENSG00000232855 (novel transcript) [ 75 ]; (2) ENSG00000272512 (novel transcript) [ 76 ]; (3) KCNJ2 antisense RNA 1 (KCNJ2-AS1) [ 77 , 78 , 79 ]; (4) KLHDC7B divergent transcript (KLHDC7B-DT) [ 80 , 81 , 82 ]; (5) long intergenic non-protein-coding RNA 2015 (LINC02015) [ 83 , 84 ]; (6) long intergenic non-protein-coding RNA 2381 (LINC02381) [ 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 ]; (7) long intergenic non-protein-coding RNA 2541 (LINC02541) [ 94 ]; (8) serpin family B member 9 pseudogene 1 (SERPINB9P1) [ 95 , 96 , 97 ]; and (9) USP30 antisense RNA 1 (USP30-AS1) [ 98 , 99 , 100 ]. However, only the functions of the lncRNA genes LINC02381 and USP30_AS1 are known, with the former known to bind transcription factors [ 85 ], RNA-binding proteins [ 86 ], and miRNAs [ 87 , 88 , 89 , 90 , 91 , 92 , 93 ]; while USP30-AS1 acts as a miRNA sponge [ 98 , 99 ] and is involved in the cis-regulation of the nearby protein-coding genes USP30 and ANKRD13A [ 100 ].…”
Section: Resultsmentioning
confidence: 99%
“…The rs142696488 variant of the PABPC4L gene indicated the highest significance (discovery, p = 1.17 × 10 −5 ; combination, p = 5.54 × 10 −7 ) with HKD, but it did not show a strong LD with surrounding SNPs at the 4q28.3 position ( Table 2 , Figure S2 ). The ANKRD26P3 gene (near LINC00421 gene) at the 13q12.11 position was associated with post-menopausal osteoporosis [ 33 ] and large artery atherosclerosis (LAA) [ 34 ]. LAA is a systemic disease that narrows arteries due to risk factors such as hypertension, diabetes and hyperlipidemia [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other than miRNAs, lncRNAs are also involved in PMOP. An RNA sequencing study reported differentially expressed lncRNAs and mRNAs in patients with PMOP (Fei et al, 2018; Wang, 2020). Lnc‐AK077216 was found to be upregulated in PMOP, which is involved in osteoclast differentiation and function with overexpression of osteoclast marker genes such as NFATc1 and CTSK (C. Liu, Cao, et al, 2019).…”
Section: Ncrnas In Women's Healthmentioning
confidence: 99%